Pain and Function in the Runner a Ten (din) uous Link - Peter Francis; Isobel Thornley; Ashley Jones; Mark I. Johnson (Medicina, 2020)
A male runner (30 years old; 10-km time: 33 min, 46 s) had been running with suspected insertional Achilles tendinopathy (AT) for ~2 years when the pain reached a threshold that prevented running. Diagnostic ultrasound (US), prior to a high-volume stripping injection, confirmed right-sided medial insertional AT. The athlete failed to respond to injection therapy and ceased running for a period of 5 weeks. At the beginning of this period, the runner completed the Victoria institute of sports assessment−Achilles questionnaire (VISA-A), the foot and ankle disability index (FADI), and FADI sport prior to undergoing an assessment of bi-lateral gastrocnemius medialis (GM) muscle architecture (muscle thickness (MT) and pennation angle (PA); US), muscle contractile properties (maximal muscle displacement (Dm) and contraction time (Tc); Tensiomyography (TMG)) and calf endurance (40 raises/min). VISA-A and FADI scores were 59%/100% and 102/136 respectively. Compared to the left leg, the right GM had a lower MT (1.60 cm vs. 1.74 cm), a similar PA (22.0° vs. 21.0°), a lower Dm (1.2 mm vs. 2.0 mm) and Tc (16.5 ms vs. 17.7 ms). Calf endurance was higher in the right leg compared to the left (48 vs. 43 raises). The athlete began a metronome-guided (15 BPM), 12-week progressive eccentric training protocol using a weighted vest (1.5 kg increments per week), while receiving six sessions of shockwave therapy concurrently (within 5 weeks). On returning to running, the athlete kept daily pain (Numeric Rating Scale; NRS) and running scores (miles*rate of perceived exertion (RPE)). Foot and ankle function improved according to scores recorded on the VISA-A (59% vs. 97%) and FADI (102 vs. 127/136). Improvements in MT (1.60 cm vs. 1.76 cm) and PA (22.0° vs. 24.8°) were recorded via US. Improvements in Dm (1.15 mm vs. 1.69 mm) and Tc (16.5 ms vs. 15.4 ms) were recorded via TMG. Calf endurance was lower in both legs and the asymmetry between legs remained (L: 31, R: 34). Pain intensity (mean weekly NRS scores) decreased between week 1 and week 12 (6.6 vs. 2.9), while running scores increased (20 vs. 38) during the same period. The program was maintained up to week 16 at which point mean weekly NRS was 2.2 and running score was 47.